An Enhanced Healthcare System - SWATHI G (2009)
INTERNAL GUIDE : Sreedevi N . EXTERNAL GUIDE : Sarvana Rajan USN No : 1MJ08SCS17 CARRIED OUT AT : Celestial V Solutions Bangalore- ACC NO : PC93
Keywords: M. Tech Computer Science